Performance of SARC-F in Regard to Sarcopenia Definitions, Muscle Mass and Functional Measures - Bahat, Gülistan; Yilmaz, O.; Kiliç, C.; Oren, M.M.; Karan, M.A. (The Journal of nutrition, health & aging, 2018)
To assess the reliability and validity of Turkish version of SARC-F in regard to screening with current definitions of sarcopenia, muscle mass and functional measures. Cross-sectional study. Community-dwelling older adults aged >=65 years admitting to a geriatric outpatient clinic. Muscle mass (bioimpedance analysis), handgrip strength, usual gait speed, chair sit-to-stand test, functional reach test, short physical performance battery, SARC-F questionnaire, FRAIL questionnaire Sarcopenia was evaluated with 4 current different definitions: European Working Group on Sarcopenia in Older People's (EWGSOP); Foundation for the National Institutes of Health (FNIH), International Working Group on Sarcopenia (IWGS) and Society on Sarcopenia, Cachexia and Wasting Disorders (SCWD). After cross-cultural adaptation, 207 subjects were analysed in the clinical validation study. Mean age was 74.6±6.7 years, 67.6% were women. Against EWGSOP, FNIH, IWGS and SCWD definitions of sarcopenia, sensitivity of SARC-F were %25, 31.6%, 50% and 40%; specificity were 81.4%, 82.4%, 81.8% and 81.7%, respectively. Positive predictive values were between 5.1-15.4% and negative predictive values were 92.3-98.2%. Against parameters of low muscle mass, sensitivity were about 20% and specificity were about 81%. Against parameters of function; for low hand grip strength, sensitivity of SARC-F were 33.7% (for Turkish cut-off); 50% (for FNIH cut-off); specificity were 93.7% (for Turkish cut-off) and 85.8% (for FNIH cut-off). Against low UGS, poor performance in chair sit to stand test, functional reach test, SPPB and presence of positive frailty screening sensitivity were 58.3%, 39.2%, 59.1%, 55.2% and 52.1% while specificity were 97.3%, 97.8%, 88.1%, 99.3% and 91.2%, respectively. The psychometric performance of Turkish SARC-F was similar to the original SARC-F. It revealed low sensitivity but high specificity with all sarcopenia definitions. Sensitivity and specificity were higher for muscle function tests reflecting its inquiry and input on functional measures. Our findings suggest that SARC-F is an excellent test to exclude muscle function impairment and sarcopenia. SARC-F is relatively a good screening test for functional measures.